Polarization control of a quantum cascade laser - Dhirhe, D.; Slight, T.; Holmes, B.; Hutchings, D.; Ironside, Charlie (2012)
By integrating a polarization mode converter we have obtained significant amounts of Transverse Electrical light from a quantum cascade laser. First results indicate up to around 18%TE light in an elliptically polarized output.